If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 12 + -9x = 15 + -15x + 13x + -3 Reorder the terms: 12 + 7x + -9x = 15 + -15x + 13x + -3 Combine like terms: 7x + -9x = -2x 12 + -2x = 15 + -15x + 13x + -3 Reorder the terms: 12 + -2x = 15 + -3 + -15x + 13x Combine like terms: 15 + -3 = 12 12 + -2x = 12 + -15x + 13x Combine like terms: -15x + 13x = -2x 12 + -2x = 12 + -2x Add '-12' to each side of the equation. 12 + -12 + -2x = 12 + -12 + -2x Combine like terms: 12 + -12 = 0 0 + -2x = 12 + -12 + -2x -2x = 12 + -12 + -2x Combine like terms: 12 + -12 = 0 -2x = 0 + -2x -2x = -2x Add '2x' to each side of the equation. -2x + 2x = -2x + 2x Combine like terms: -2x + 2x = 0 0 = -2x + 2x Combine like terms: -2x + 2x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 3(4x-1)=25 | | 13x+7-3x=4x-10 | | 95x+0=70x+70*450 | | m^2+5m+6= | | -3+y+6=5y+19 | | 7x+16=8x+7 | | c=qn+q | | 8x-(6x+7)=3 | | x+(x+3)+(x+7)=40 | | .3(x)+150(.5)=.5 | | 0.1*x+0.6*40=0.4 | | .1(x)+.6(40)=.4 | | 24x-5-18x+2=18-7-12x+15 | | 89x+8(82)=87(x+8) | | 89(X)+8(82)=87(x+8) | | x+3/4+9=0 | | x+(-11/2)+9=0 | | 5x^2=60-20x | | 2w^2-128=0 | | 3x-4=2(3x+2)-3x | | 3x^2+84=33x | | -8/3+y+9=0 | | 6x+7-9x=16-14x+11-9 | | 200+1x=160+4x | | log(x-9)=1-logx | | log(x-0)=1-logx | | (2y+7)(5+y)=0 | | 64-9u^2= | | -3x-10x=-52 | | 3(w+2)+w=4(w-1)+9 | | 12x-9=15x-3 | | -3(u+2)=2(u+6)+7 |